2014
DOI: 10.1016/j.jiac.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparative study of recombinant human thrombomodulin and gabexate mesilate in sepsis-induced disseminated intravascular coagulation patients

Abstract: The novel biological agent recombinant human thrombomodulin (rhTM) has been used clinically in Japan to treat disseminated intravascular coagulation (DIC) since 2008.Previous studies have shown the efficacy of rhTM versus heparin therapy or non-rhTM therapy. We retrospectively evaluated and compared the efficacies of rhTM and gabexate mesilate (GM) in patients diagnosed with sepsis-induced DIC. From September 2010 to October 2012, patients with sepsis-induced DIC who were treated with rhTM (n = 13) or GM (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Recently, the clinical effects of ART-123 in patients with sepsisinduced DIC were reported (9)(10)(11)(12)(13)(14). In our multicentre, retrospective, large-scale study, 45 % of sepsis-induced DIC patients treated with ART-123 had undergone renal replacement therapy (12).…”
Section: Introductionmentioning
confidence: 82%
“…Recently, the clinical effects of ART-123 in patients with sepsisinduced DIC were reported (9)(10)(11)(12)(13)(14). In our multicentre, retrospective, large-scale study, 45 % of sepsis-induced DIC patients treated with ART-123 had undergone renal replacement therapy (12).…”
Section: Introductionmentioning
confidence: 82%
“…Previous studies have reported that these resolution rates were 55.1% (n = 216) and 57.8% (n = 135), respectively, [ 17 ] thus at our institution, the DIC resolution rates were markedly better than that previously reported. For infectious diseases, some reports indicated that rTM was more effective [ 20 , 23 ] and that it significantly reduced mortality and increased survival compared with GM. [ 22 , 30 , 31 ] In the setting of hematologic malignancies, Takezako et al revealed that OS was superior in AML patients treated with rTM when compared with heparin.…”
Section: Discussionmentioning
confidence: 99%
“…Gabexate mesilate (GM), a synthetic protease inhibitor (SPI), was previously used routinely for treating DIC before rTM was approved in Japan, although no clinical trials have been reported assessing its efficacy for treating DIC. [ 20 ] Recent studies have indicated that rTM is more effective than GM for treating DIC in patients with infectious diseases; [ 21 – 23 ] conversely, little research has been conducted among AML patients. Therefore, we retrospectively evaluated the efficacy of rTM compared to that of GM for treating AML patients complicated with DIC.…”
Section: Introductionmentioning
confidence: 99%
“…Takazono et al (12) evaluated and compared the clinical efficacies of rTM and GM for the treatment of sepsis-induced DIC. In that study, the platelet counts of the rTM group significantly improved compared to the GM group.…”
Section: Discussionmentioning
confidence: 99%